Investigating the Effect of Aluminum Diethylphosphinate on Thermal Stability, Flame Retardancy, and Mechanical Properties of Poly(butylene succinate) - Wang, Yiming; Jiang, Dayong; Wen, Xin; Tang, Tao; Szymańska, Karolina; Sielicki, Krzysztof; Wenelska, Karolina; Mijowska, Ewa (Frontiers in Materials, 2021)
Poly(butylene succinate) is one of the most promising biodegradable polymers, but its applications are limited by poor flame retardancy. In this work, poly(butylene succinate)/diethylphosphinate (PBS/AlPi) composites were fabricated to investigate the effect of AlPi on their thermal stability, flame retardancy and mechanical properties. It was found that high content of AlPi decreased the thermal stability of PBS, and the decrease became stronger under air atmosphere. When the content of AlPi reached to 25wt%, the flame retardancy was improved with limited oxygen index (LOI) of 29.5%, V0 rating in UL-94 vertical burning test and 49.3% reduction on the peak of heat release rate (PHRR) in cone calorimeter test. Meanwhile, the addition of AlPi could improve mechanical properties of PBS with high tensile strength and Young’s modulus, which was ascribed to the compatible effect of maleic anhydride-grafted poly(butylene succinate) (PBS-g-MA) with good filler dispersion and strong matrix-particles interaction. Thus, the AlPi was an effective flame retardant to PBS, so that PBS/AlPi composites displayed excellent flame retardancy without seriously sacrificing other comprehensive performances.